The Newest Trends in the Development of the Eastern Asia's and Latin America's Economies (Czech Journal of International Relations, 2024)
Vladimir Slunečko:born 1961, graduated from the University of Economics. He is currently a skilled employee of C-VEV. It deals with the issues of developing countries.